Evaluation of groundwater as a domestic water resource for rural villages in the Eastern Cape near Matatiele - Ramakoae, Motselisi (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.